Nanosecond laser ablation and deposition of silicon - Siew, Wee Ong; Yap, Seong Shan; Ladam, Cécile; Dahl, Øystein; Reenaas, Turid Worren; Tou, Teck Yong (2011)
Nanosecond-pulsed KrF (248 nm, 25 ns) and Nd:YAG (1064 nm, 532 nm, 355 nm, 5 ns) lasers were used to ablate a polycrystalline Si target in a background pressure of < 10(-4) Pa. Si films were deposited on Si and GaAs substrates at room temperature. The surface morphology of the films was characterized using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Round droplets from 20 nm to 5 mu m were detected on the deposited films. Raman Spectroscopy indicated that the micron-sized droplets were crystalline and the films were amorphous. The dependence of the properties of the films on laser wavelengths and fluence is discussed.